Role of Nutrition in Inflammatory Bowel Disease (IBD): New Therapeutic Approaches and Recent Outcomes - Hernández, Nallely Bueno; MañeAlmero, Josep; Cortes, Isabel; Yamamoto-Furusho, Jesús (Journal of Nutritional Therapeutics, 2013)
Inflammatory bowel disease (IBD) is the generic term given to a heterogeneous group of disorders of the gastrointestinal tract that are characterized by chronic inflammation. The major forms of IBD are Crohn’s disease (CD) and ulcerative colitis (UC), which are increasing in incidence, prevalence and severity in many countries; these are characterized by intestinal inflammation and are believed to involve complex interactions between genetic, immunological and environmental factors. The incidence continues to rise, both in low and in high-incidence areas. Several dietary regimes may modify disease symptoms, in part through their actions on the host microbe. However, other dietary factors could affect the microbiotic or genetic expression in IBD patients in different ways. The purpose of this review is to discuss the most recent evidence from the literature on the use of nutritional therapy in the treatment of IBD and to review the role of environmental factors on the progressive increase of prevalence. The epidemiological data reveal an increasing incidence of IBD in recent years, which may be the result of increased intake of simple sugars and consumption disproportionate of fat (saturated and unsaturated). Intestinal permeability and inflammation could improve with proper diet in protein, probiotics and FA (n-3 and n-6). Diet and the host microbiota are likely to play important but as yet poorly defined roles therefore, is necessary to continue investigating to implement molecular findings in clinical treatments or adjunctive therapies.